Development of Snakes and Ladders Learning Media on Vector Material: Analysis Using the Rasch Model - Dwi Endah Elfiana; Shobrina Nurul Mufida; Oky Dua Oktaningtyas; Qoimatul Mustaghfiroh; Ummiy Fauziyah Laili; Dyah Permata Sari; Iqbal Ainun Najib; Melan Nuraini; Sela Rizkiyatus Sholiha; Arin Amelia Azzahra; M. Satria Alif Sa’ban (National Dong Hwa University, 2025)
This study aims to develop snakes and ladders learning media for vector materials in physics and to assess its feasibility using the Rasch Model. The research uses a research and development approach with the ADDIE model, emphasizing limited feasibility testing. The study involved 35 high school students (12 male and 23 female) at the implementation stage. Research data were obtained through expert validation sheets and student response questionnaires. Media validation consisted of three subject matter experts, three learning media experts, and three physics education experts. The collected data were analyzed using the Many Facet Rasch Model to evaluate item fit, rater consistency, and the reliability of the assessment instruments. The results showed that the validation data met the fit statistics and acceptable reliability criteria, indicating uniformity of assessment among the validators across various evaluated aspects. Analysis of student responses revealed that the snakes and ladders learning media developed met the practicality criteria from a student perspective after being implemented in vector learning activities. Students assessed this media as easy to use and suitable for supporting physics learning. These findings indicate that the developed learning media is feasible in terms of content, design, and learning aspects. The application of the Rasch Model strengthens the objectivity of the feasibility analysis by controlling the level of assessor rigor and item characteristics.